DISCIPLINING WOMEN̓S BODIES - Sojo Mora, Blanca Luz (2019)
This article determines the actions that women perform to control their body, as well as the reasons why they use corporal discipline. In this study, an interview was conducted with 14 participants. It was found that the women interviewed perform various actions to discipline their body, the main one being physical activity. It was also found that this discipline is related to body dissatisfaction, concern for appearance and gender norms. In conclusion, women discipline their bodies to have a “feminine and attractive appearance” according to social aesthetic ideals.